Entrepreneurship and Economic Growth 2006
DOI: 10.1093/acprof:oso/9780195183511.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Capital and Economic Performance

Abstract: Die Discussion Papers dienen einer möglichst schnellen Verbreitung von neueren Forschungsarbeiten des ZEW. Die Beiträge liegen in alleiniger Verantwortung der Autoren und stellen nicht notwendigerweise die Meinung des ZEW dar.Discussion Papers are intended to make results of ZEW research promptly available to other economists in order to encourage discussion and suggestions for revisions. The authors are solely responsible for the contents which do not necessarily represent the opinion of the ZEW.Download this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
226
0
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(243 citation statements)
references
References 243 publications
3
226
0
14
Order By: Relevance
“…One could even argue that high rates of investment in human and physical capital are themselves stimulated by effective innovation, and cannot be maintained in the absence of innovation. Recent studies emphasize entrepreneurship as a driver of economic development and some authors include entrepreneurship as a fourth production factor in the macroeconomic production function (Audretsch and Keilbach 2004). Entrepreneurship is the factor that creates wealth by combining existing production factors in new ways.…”
Section: Entrepreneurship and Economic Developmentmentioning
confidence: 99%
“…One could even argue that high rates of investment in human and physical capital are themselves stimulated by effective innovation, and cannot be maintained in the absence of innovation. Recent studies emphasize entrepreneurship as a driver of economic development and some authors include entrepreneurship as a fourth production factor in the macroeconomic production function (Audretsch and Keilbach 2004). Entrepreneurship is the factor that creates wealth by combining existing production factors in new ways.…”
Section: Entrepreneurship and Economic Developmentmentioning
confidence: 99%
“…Thus, all the positive effects of entrepreneurship and new firm start-ups underlined above would be particularly obvious at the regional level (see Lee, Florida and Acs, 2004) where it has been found that interspatial variations in the endowment of "entrepreneurship capital" may be an important determinant of differences in regional output, knowledge spillovers and productivity (see Audretsch and Keilbach, 2004b;Varga and Schalk, 2004 (OECD, 2003, p. 145). In a previous paper with David Audretsch (Audretsch, Santarelli and Vivarelli, 1999a), we studied 1,570 new Italian manufacturing firms 3 and tracked their post-entry evolution for six years.…”
Section: The Aggregate Outcomes Of Industrial Dynamicsmentioning
confidence: 99%
“…From such a perspective, entrepreneurs are those individuals Schumpeter labelled "energetic types" who display their "essential features" by introducing the "new" into various activities and by "breaking with the established routines" usually adhered to by managers (see Santarelli, 2006a, p. xii). Thus, entrepreneurship deals with the role of risk takers and creative individuals who start a new business or revive an already existing one (see Hébert and Link, 1999) 2 .In more general terms, it has been argued that new firm formation can be beneficial for economic growth (at least in developed countries, see Van Stel, Carree and Thurik, 2005), employment generation and unemployment reduction (see Hart and Oulton, 2001;Thurik, 2003;Baptista, Van Stel and Thurik, 2006).It has long been observed that entrepreneurial activity varies across geographic space.Thus, all the positive effects of entrepreneurship and new firm start-ups underlined above would be particularly obvious at the regional level (see Lee, Florida and Acs, 2004) where it has been found that interspatial variations in the endowment of "entrepreneurship capital" may be an important determinant of differences in regional output, knowledge spillovers and productivity (see Audretsch and Keilbach, 2004b;Varga and Schalk, 2004 (OECD, 2003, p. 145). In a previous paper with David Audretsch (Audretsch, Santarelli and Vivarelli, 1999a), we studied 1,570 new Italian manufacturing firms 3 and tracked their post-entry evolution for six years.…”
mentioning
confidence: 99%
“…The notion, that innovation, entrepreneurship and knowledge, acquired through research and education, can drive economic growth, is currently well-grounded in economic research [2], [3], [4] and [5]. However, in the present author's view, enhancing growth requires not only public and private resources, but also a challenging business culture, enhanced by awareness and provision of various training programs in entrepreneurship and innovation.…”
Section: Literature Reviewmentioning
confidence: 97%